2002
DOI: 10.1177/089686080202200316
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Metabolism in Patients on Continuous Ambulatory Peritoneal Dialysis

Abstract: Background Selenium is an essential trace element for living organisms. In many publications, researchers express concern about a possible Se deficiency in patients with end-stage chronic renal failure (ESCRF) undergoing continuous ambulatory peritoneal dialysis (CAPD). However, in a number of published articles, the data provide no evidence that patients under CAPD develop Se deficiency. Objective We investigated Se metabolism in ESCRF patients on CAPD. Setting The study was carried out at the Department of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…They found that, although serum selenium levels were low in patients with renal failure, there was no correlation between plasma and urinary selenium levels, and urinary selenium excretion was lower than in a control population. Numerous other studies have explored serum or plasma selenium status in renal failure10–16. These have all shown low selenium levels in patients with renal failure; however, there is disagreement as to whether or not the relationship is dialysis dependent and whether selenium levels are lower in patients undergoing peritoneal haemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…They found that, although serum selenium levels were low in patients with renal failure, there was no correlation between plasma and urinary selenium levels, and urinary selenium excretion was lower than in a control population. Numerous other studies have explored serum or plasma selenium status in renal failure10–16. These have all shown low selenium levels in patients with renal failure; however, there is disagreement as to whether or not the relationship is dialysis dependent and whether selenium levels are lower in patients undergoing peritoneal haemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…Selenium is not removed by PD in significant quantities (100). One study of PD patients suggests that there was no clinical evidence for functional deficiency and that low serum albumin may contribute to low serum measurements, because selenium binds to albumin electrostatically (101).…”
Section: Trace Element Concentrations: What Do They Mean?mentioning
confidence: 99%
“…X-Ray methods have been used for selenium analysis the last few years as selenium ionization cross section is quite high if an ionization source in the 17-22 keV energy region is used. 7 Total reflection X-ray fluorescence (TXRF) is a rather new technique in elemental analysis. It is an economical method (low cost per sample) that provides reliable analytical results concerning the analyses of trace elements in liquid or solid samples.…”
Section: Introductionmentioning
confidence: 99%